Rehabilitation Intervention for Individuals With Heart Failure and Fatigue to Reduce Fatigue Impact: A Feasibility Study - Kim, Young Joo (Ann Rehabil Med, 2019)
OBJECTIVE: To investigate feasibility of recruitment, tablet use in intervention delivery, and use of self-report outcome measures and to analyze the effect of Energy Conservation plus Problem-Solving Therapy versus Health Education interventions for individuals with heart failure-associated fatigue. METHODS: This feasibility study was a block-randomized controlled trial involving 23 adults, blinded to their group assignment, in a rural southern area in the United States. Individuals with heart failure and fatigue received the interventions for 6 weeks through videoconferencing or telephone. Participants were taught to solve their fatigue-related problems using energy conservation strategies and the process of Problem-Solving Therapy or educated about health-related topics. RESULTS: The recruitment rate was 23%. All participants completed the study participation according to their group assignment, except for one participant in the Energy Conservation plus Problem-Solving Therapy group. Participants primarily used the tablet (n=21) rather than the phone (n=2). Self-report errors were noted on Activity Card Sort (n=23). Reported fatigue was significantly lower for both the Energy Conservation plus Problem-Solving Therapy (p=0.03, r=0.49) and Health Education (p=0.004, r=0.64) groups. The Health Education group reported significantly lower fatigue impact (p=0.019, r=0.48). Participation was significantly different in low-physical demand leisure activities (p=0.008; r=0.55) favoring the Energy Conservation plus Problem-Solving Therapy group. CONCLUSION: The recruitment and delivery of the interventions were feasible. Activity Card Sort may not be appropriate for this study population due to recall bias. The interventions warrant future research to reduce fatigue and decrease participation in sedentary activities (Clinical Trial Registration number: NCT03820674).